PENGARUH KONSUMSI MENGKUDU TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI: SYSTEMATIC REVIEW - La Ode Alifariki (NHM PRESS, 2022)
Hypertension or high blood pressure is a medical condition characterized by increased contractions. Arteries that exceed 140/90 mmHg at rest are confirmed to have high blood pressure. Non-pharmacological treatment of hypertension can use herbal plants, such as noni fruit. The purpose of this study was to determine the effect of giving noni on blood pressure in patients with hypertension. This study was limited from 2014 to 2022 and found 9 eligible articles sourced from the Google Scholar search engine with the keywords “noni, blood pressure AND hypertension. The results of the study reported that from 9 articles found noni fruit was effective in lowering blood pressure in patients with hypertension.